The Impact Of Information Technology On Teaching And Learning In Institutions Of Higher Learning - Poh, Lye Kim (2004)
The purpose of this study is to look into the impact of IT on Teaching and learning in Institution of Higher learning in three aspects: i. Does the use of IT make learning more accessible? ii. Does the use of IT promote improve learning. iii. What are the barriers for a successful integration of IT into education?